2007
DOI: 10.1007/s00420-007-0241-9
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic potential of formaldehyde in occupational settings: a critical assessment and possible impact on occupational exposure levels

Abstract: Current occupational exposure levels to formaldehyde, set to protect against local irritation, should not be adapted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Formaldehyde is considered to be a carcinogenic compound in humans, even if the evidence of an association between occupational formaldehyde exposure and nasopharyngeal cancer is still under debate [9,10]. On the basis of a thorough analysis of existing epidemiological studies and the plausibility of biological mechanisms resulting from experimental studies, formaldehyde has been considered as a carcinogenic compound in humans [6].…”
Section: Health Effectsmentioning
confidence: 99%
“…Formaldehyde is considered to be a carcinogenic compound in humans, even if the evidence of an association between occupational formaldehyde exposure and nasopharyngeal cancer is still under debate [9,10]. On the basis of a thorough analysis of existing epidemiological studies and the plausibility of biological mechanisms resulting from experimental studies, formaldehyde has been considered as a carcinogenic compound in humans [6].…”
Section: Health Effectsmentioning
confidence: 99%
“…Further more, there are cohort and case-control studies investigating the association between occupational exposure to formaldehyde and Nasopharyngeal Cancer (NPC) and reporting estimates of formaldehyde exposure as well as the most recent meta-analyses [53] . Results of the cohort studies reviewed by Duhayon reported that mortality from NPC was elevated compared with that of the US general population [54] . However, internal comparison analysis using alternative categorization revealed that none of the relative risk for NPC was statistically significantly increased in any category of exposure.…”
Section: Health Effect To Humanmentioning
confidence: 99%
“…For cancer effect studies, formaldehyde was long considered as a potential human carcinogen (Group 2A chemical) based on experimental animal studies and limited evidence of human carcinogenicity. However, formaldehyde was reclassified as a human carcinogen (Group 1) by the International Agency for Research on Cancer (IARC) in June 2004 based on "sufficient epidemiological evidence that formaldehyde causes nasopharyngeal cancer in humans" [53,54] . Further more, there are cohort and case-control studies investigating the association between occupational exposure to formaldehyde and Nasopharyngeal Cancer (NPC) and reporting estimates of formaldehyde exposure as well as the most recent meta-analyses [53] .…”
Section: Health Effect To Humanmentioning
confidence: 99%
“…Several recent studies have shown an increased risk of major fetal malformations in pregnant women who work with organic solvents occupationally (Khattak et al, 1999;Till et al, 2001;Bedino, 2002;Laslo-Baker, 2004, Chevrier et al, 2006; et al, , Garlantezec et al, 2009. While much of the recent research specifically on formaldehyde has dealt with its possible relationship to nasopharyngeal, sinonasal, and oral cancers (Coggon et al, 2003;Arts et al, 2006;Bosetti et al, 2008;Duhayon et al, 2008; National Toxicology Program, 2010), and lymphohematopoietic malignancies Hauptmann et al, 2009), there are several studies, which have focused on its potential reproductive effects. Formaldehyde has been indicted as a reproductive hazard to those who work with it at high concentration, such as wood industry workers, cosmetologists, and embalmers (John et al, 1994;Taskinen et al, 1999;Bedino, 2002).…”
mentioning
confidence: 98%